Between policy and practice: Assessing implementation gaps in adaptive sex education for adolescents with intellectual disabilities - Nanin Ardiyanti; Sudiyatno Sudiyatno; Widowati Pusporini (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aimed to evaluate the implementation of the adaptive sex education program at SLB Negeri Manggar, the only special needs school in East Belitung Regency, Indonesia. Despite legal mandates and the recognized vulnerability of adolescents with intellectual disabilities to sexual violence and exploitation, a significant gap exists between the policy intent and the practical, standardized delivery of adaptive sex education in special schools. Challenges such as insufficient teacher training, limited parental support, and a lack of dedicated curriculum guidelines hinder effective program implementation. Using the CIPP (Context, Input, Process, Product) evaluation model, this research focused specifically on the input (educator quality, facilities, stakeholder support) and process (integration, teaching methods, material delivery) components. A mixed-methods sequential explanatory design was employed, collecting quantitative data via questionnaires from 20 students and 20 parents, and qualitative data through in-depth interviews with five teachers and one vice-principal. Results indicate that the program is well-implemented overall (process achievement score: 80%). Educator competence and facility availability were categorized as